Amalgamated cross-species transcriptomes reveal organ-specific propensity in gene expression evolution - Kenji Fukushima (Nature Portfolio, 2020)
Multicellularity requires complex coordinated gene expression. Fukushima and Pollock find that gene expression in different organs is likely to constrain future patterns of gene expression evolution, particularly following gene duplication.